Sejarah Sakramen Penguatan dan Teologi Sakramen Penguatan menurut Thomas Aquinas - Budiarjo, Mikhael Wicaksono (Felicitas, 2024)
As one of the sacraments of initiation in the Catholic Church, the Sacrament of Confirmation has an important spiritual element for the salvific work of Christians. The role of the third person of God, the Holy Spirit, often appears in the liturgy of this sacrament. This sacrament has a physical sign in the form of anointing oil that has a deep meaning from its historical, biblical and theological background. The theology of the sacrament of chrismation developed with one of them being elaborated by St. Thomas Aquinas in Summa Theologiae. In Summa Theologiae, there are several basic theological concepts of this sacrament of confirmation. From this history and theology, the sacrament of chrismation has a meaning that brings Christians to maturity in faith.